CLINICAL INDICATORS OF THE EFFECTIVENESS OF TREATMENT OF ORAL LEUKOPLAKIA (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The study included 40 patients (20 men and 20 women) aged 35 to 65 years with a clinically and histologically confirmed diagnosis of leukoplakia. Inclusion criteria: the presence of leukoplakia foci on the mucous membrane of the cheeks, tongue, and floor of the oral cavity. Patients after surgical treatment of leukoplakia of the oral mucosa were prescribed KIN Care gel for topical use 2 times a day after oral sanitation for 8 days.